Strategi Pengembangan Kurikulum dan Sarana Prasarana Ma’had Aly Pondok Quran Bandung - Hidayat, Ara; Seftiani, Rizka Dwi (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
This research is a follow-up study from previous research on strategic planning to establish Ma’had Aly Pondok Quran in Bandung. This research focused on the curriculum and facilities in Ma’had Aly Pondok Quran in Bandung. Using descriptive qualitative field research, the data is collected through documentation, observation, and interviews. The data is analyzed utilizing strategic factors analysis summary. The subject of the research is the head of Ma'had Aly Pondok Quran, the Muhafizh, the person in charge of the development of human resources and infrastructure of Ma'had Aly Pondok Quran, also twenty Ma’had Aly students. The results showed that the standard content of the material in Ma'had Aly curriculum still needed to be added and adjusted to support the legality of Ma'had Aly. The material that needs to be added in Ma'had Aly Pondok Quran is Manhaj Da'wah, Tafsir, Ulumul Qur'an and its branches of knowledge, Tauhid, Worship Fiqh, Computers, English, and Research Methodology. Whereas the infrastructure facilities of Ma'had Aly Pondok Quran which are the priority in development are pesantren dormitories for man and classes to support learning. Keywords: Institutional Development Strategy, Curriculum, Infrastructure, Ma’had Aly